2020
DOI: 10.21014/acta_imeko.v9i2.800
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning techniques and empirical mode decomposition for the classification of analog modulated signals

Abstract: <!--[if gte mso 11]><w:PermStart w:id="205147274" w:edGrp="everyone"/><![endif]--><p class="Abstract">In this article, an automatic Analog Modulation Classifier based on Empirical mode decomposition and Machine learning approaches (AMC-EM) is proposed. The AMC-EM operates without a priori information and can recognise typical analog modulation schemes: amplitude modulation, phase modulation, frequency modulation, and single sideband modulation. The AMC-EM uses Empirical Mode Deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For the given order and time delay, a spectrum-sensing and power recognition framework based on highorder cumulants (HCs) [19] was developed, which can eliminate the adverse impact of noise power uncertainty. Carnì et al [20] confirmed that SVMs driven by empirical mode decomposition (EMD-SVM) can identify typical analog modulation schemes, including amplitude modulation (AM), phase modulation (PM), frequency modulation (FM), and single-sideband modulation (SSB) without prior information. By combining the theories of cyclostationarity and entropy, an SVM driven by hybrid features, cyclostationarity, and information entropy (HCI-SVM) [21] was introduced to recognize digital modulation schemes.…”
Section: Lb and Fb Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the given order and time delay, a spectrum-sensing and power recognition framework based on highorder cumulants (HCs) [19] was developed, which can eliminate the adverse impact of noise power uncertainty. Carnì et al [20] confirmed that SVMs driven by empirical mode decomposition (EMD-SVM) can identify typical analog modulation schemes, including amplitude modulation (AM), phase modulation (PM), frequency modulation (FM), and single-sideband modulation (SSB) without prior information. By combining the theories of cyclostationarity and entropy, an SVM driven by hybrid features, cyclostationarity, and information entropy (HCI-SVM) [21] was introduced to recognize digital modulation schemes.…”
Section: Lb and Fb Methodsmentioning
confidence: 99%
“…FB methods accomplish the AMC task by constructing feature-driven machine learning classifiers. Commonly used features include cyclostationary features [18], high-order cumulants [19], and intrinsic mode functions (IMFs) [20]. The classifiers can be support vector machines (SVMs) [21], random forest (RF) [22], neural networks (NNs) [23] etc., FB methods can be easily deployed, but the design of features is labor-intensive and difficult to generalize well to different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The higher classification accuracy arises from the robustness of the HHT in the analysis of the non-stationarity signal and of the CNN to operate on noisy data. For the evaluation of the parameters of the event, in [ 44 ], the authors propose a tool based on the analysis of Intrinsic Mode Functions (IMFs) resulting from the EMD [ 45 , 46 , 47 ]. This decomposition is the basis through which the HHT is evaluated, so the same advantages of the HHT are provided by this procedure.…”
Section: Central Classification Unitmentioning
confidence: 99%
“…Emotional recognition is considered a major theme in machine learning and Artificial Intelligence (AI) [1] in recent years. The huge upsurge in the creation of advanced interaction technologies between humans and computers has further encouraged progress in this area [2].…”
Section: Introductionmentioning
confidence: 99%